New leverage over macroeconomic policy: the phenomenon of clusters - Valentinas Navickas; Asta Malakauskaitė (Business: Theory and Practice, 2008)
The impact of government on macroeconomic processes is pretty relevant. It manifests itself through various functions of governance and administration. The main mission of governing bodies is to assure both – economic and political stability. Government is also responsible for improving the microeconomic capabilities of companies by assuring efficient allocation of resources and stimulating productivity. The modern economic policy is based on the concept of clusters. The aim of the study is to analyze the importance of clusters in the context of macroeconomic policy. When a government implements a cluster-based economic policy, it actively participates in the process of creating and improving strategic relations inside and outside the cluster. That kind of policy is more efficient than any economic policy aimed at individual companies, as it enables a government to influence a great number of companies without distorting market-based competitive environment.